Hippies as a Metaphor for Ambiguity or Why they are Blamed for the Rise of "Gender Ideology" in Costa Rica - Sequeira Rovira, Paula (2020)
This article seeks to analyze the ideas related to the emergence of hippies in Costa Rica to understand the current annoyances of conservative groups on this counterculture. It will not only be sought to analyze part of the reactions and actions that were taken against them, but also to understand how and why "gender ideology" was interested in them. The analysis was based on a review of the news that appeared in the newspaper La República during 1968 and 1975 and current documents in which they are taken up again. The approach of this article is that hippies are useful to these conservative sectors as a metaphor to criticize a supposed ambiguity that they perceive in current societies and that is concretized in the figure of the homosexualized child. Furthermore, it is concluded that the suggested actions for hippies or homosexualized children resort in quite different power technologies.